Computational Fluid Dynamics Analysis of the Impacts of Air Supply Velocity Modes on the Differential Pressure Precooling Efficiency of Peaches Stored in Ventilated Packaging - CHEN Yingmin, LINGHU Boxiang, ZHAO Mingzhang, SONG Haiyan (Shipin Kexue)
In this study, a numerical model for heat and mass transfer in the differential pressure precooling of peaches stored in layered packaging under different precooling conditions was constructed based on computational fluid dynamics. Through the analysis of experimental and simulation data, it was found that the maximum root mean square error (RMSE) between the constructed numerical model and the experimental group was 0.796 7 ℃, and the mean absolute percentage error (MAPE) was 6.74%, which demonstrated the feasibility and authenticity of the modeling method. The precooling efficiencies of two air supply velocity modes were compared, demonstrating that compared with the constant velocity mode, the variable velocity mode ∆P1 + ∆P2 improved the uniformity of precooling and shortened the cooling time, and there was a seven-fold threshold relationship between ∆P2 and ∆P1. When ∆P2 was more than seven times as high as ∆P1 (∆P1 < 35 Pa), the uniformity of precooling was improved by about 10%–20%, and the precooling time was shortened by 50%-75%; however, the energy consumption cost increased by at least 8 times, and it increased exponentially with ∆P2. Therefore, the variable velocity mode should be selected when priority is given to the precooling quality and the transfer time to cold storage; in which (15 + 105) Pa is the optimal environmental parameter combination for peach precooling, while the constant velocity mode should be selected to achieve energy savings in precooling. This study provides a theoretical reference for small and medium-sized orchards to reasonably select air supply modes and accurately control the precooling efficiency of fruits.